Governance Strategy for Free Nutritious Food Procurement: An Administrative Law Perspective - Zaenal Arifin; Miftah Arifin (Jurnal Wawasan Yuridika, 2025)
The Free Nutritious Food Program (MBG) is a strategic government policy to improve the quality of human resources; however, its procurement governance still raises juridical concerns that create discrepancies between das sollen and das sein. This study aims to analyze the governance of MBG procurement from the perspective of Administrative Law and to formulate procurement strategies in line with the principles of good governance. The research employs a normative juridical method with statute approach and case approaches, using primary legal materials such as Presidential Regulation No. 16 of 2018 and Presidential Regulation No. 83 of 2024, and is qualitatively analyzed. The findings reveal practices of large provider dominance, limited MSME access to the e-catalog, and weak oversight, which contradict the principles of legality, justice, and accountability. The novelty of this research lies in its assertion that MBG procurement is an administrative act (bestuursdaad) that must be examined within the framework of Administrative Law to ensure the program’s legitimacy, fairness, and sustainability.